Pengembangan Game Augmented Reality Pengenalan Baju Adat Nusantara Menggunakan Kinect Sebagai Kendali Permainan (Kasus Studi : Anak Usia 9-12 Tahun) - Yudha Hadi Pratama; Muhammad Aminul Akbar; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The introduction of traditional clothes has been done since the children enter elementary school in art and culture lessons and workshop. One of the existing basic competencies is to group identity similarities such as traditional clothes, language, traditional house, traditional food and traditional ceremony that start from grade 4 to grade 6 or around 9-12 years old. The current learning system nowadays is book, the book itself only presents some explanations and pictures of traditional clothes so that children can only read and imagine. The media they use isn't really interesting so the children get bored quickly and then they are not motivated to learn and understand the kind of traditional clothes. So to provide learning and the introduction of traditional clothes of Indonesia to the children need to be made interesting and fun media such as game. The advantage of game is the ability of the game to persuade players and motivate them to success to reach a goal. The solution based on the problem is by making an educational game to introduce traditional clothes by using augmented reality technology for more interactive. The purpose of using Augmented Reality in the development of educational games is so that children can interact directly with virtual objects to get a more real experience. The results of the development of educational games to introduce traditional clothes is very satisfactory, it is based on the results of focus testing testing and fun testing that has been done where there is an increase in the score of each child that indicates that there is learning when children play the game.